2007
DOI: 10.2460/ajvr.68.9.941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibroblast growth factor-2 on equine mesenchymal stem cell monolayer expansion and chondrogenesis

Abstract: FGF-2 treatment of bone marrow-derived MSC monolayers enhanced subsequent chondrogenic differentiation in a 3-dimensional culture. This result is important for tissue engineering strategies dependent on MSC expansion for cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 32 publications
4
69
0
1
Order By: Relevance
“…After normalizing matrix synthesis to cell number, the difference was not significant; much of the difference in matrix synthesis is attributable to the differences in cell attachment and survival over time. These results were similar to those of previous studies 44,45 of matrix synthesis by equine bone marrow-derived MSCs, in which increased synthesis reflected increases in cell numbers rather than per-cell changes. Nevertheless, this outcome is relevant to therapeutic applications because colonization of the tendon matrix and persistence at the site of administration would likely influence the clinical efficacy of these cells for treatment of horses with tendon injuries.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…After normalizing matrix synthesis to cell number, the difference was not significant; much of the difference in matrix synthesis is attributable to the differences in cell attachment and survival over time. These results were similar to those of previous studies 44,45 of matrix synthesis by equine bone marrow-derived MSCs, in which increased synthesis reflected increases in cell numbers rather than per-cell changes. Nevertheless, this outcome is relevant to therapeutic applications because colonization of the tendon matrix and persistence at the site of administration would likely influence the clinical efficacy of these cells for treatment of horses with tendon injuries.…”
Section: Discussionsupporting
confidence: 82%
“…On the basis of these data, a minimum of 12 horses would be necessary to provide sufficient power (0.8) for these analyses. However, in our experience, marked interdonor variability is a biological reality of mesenchymal cell isolation and in vitro activity 18,44,45 and is likely to be reflected in in vivo therapeutic efficacies.…”
Section: Discussionmentioning
confidence: 99%
“…The time required to generate clinically useful cell numbers could be reduced by collecting larger volumes of synovial fluid and/or by aspirating fluid from several joints, given that arthrocentesis is a minimally invasive procedure, compared to bone marrow or adipose tissue harvesting. In vitro expansion of SF-CPs can also be substantially accelerated by fibroblast growth factor-2, reducing expansion times by more than 50%, without compromising subsequent chondrogenesis [21], as with bone marrow MSCs [30]. Alternatively, endogenous SF-CPs could be directly recruited to sites of cartilage damage to improve healing, by modulating chemokine concentrations at sites of injury [2,31,32] and utilizing the intrinsic chondrogenic properties of synovial fluid [33].…”
Section: Discussionmentioning
confidence: 99%
“…Since FGF2 and IGF1 have been reported to be growth factors which enhance the proliferation or differentiation of chondrocytes and their progenitors, it could be expected that high expression of these factors contributes to repair of a cartilage defect. 24,25 However, FGF2 may also be disadvantageous for cartilage formation because of its proangiogenic and pro-osteogenic potential. Miyakoshi et al demonstrated that intra-articular administration of FGF2 induced inflammation and osteophyte formation.…”
Section: Figmentioning
confidence: 99%